Assessment on Digitalization of Basic Physics Courses: Need Analysis on the Use of Digital-based Assessment - Nurlina, N.; Marisda, D. H.; Riskawati, R.; Sultan, A. D.; Sukmawati, S.; Akram, A. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Assessment is essential to measure students' achievement of learning objectives. Assessments in Basic physics courses are still categorized as manual, unstructured, and outdated. Using descriptive statistics, this study aims to investigate the need for digital assessments in Basic physics courses. The samples were taken from two public universities, two private universities, and a university with Physics Education Study Programs. They were half of each university students’ number per class. The number of respondents from Public university A, Public university B, Private University C, Private University D, and University E were 91, 49, 25, 20, and 29 students, respectively. Data collection was carried out using a questionnaire via a google form. Data obtained was analyzed by calculating the percentage for each indicator. Research indicators consist of the availability of teaching materials, the application of blended models, students' interest in basic physics, and the availability of assessments of the physics learning process. The results show that the five institutions that provide Basic Physics courses have not implemented digital assessments optimally. Of the five tertiary institutions that became the research sample, only one institution achieved the minimum target, with a score of 55.31% in the class of 2021 at university A. Meanwhile, the other four tertiary institutions did not achieve 50% in the last five batches. Therefore, lecturers must develop digital assessments in basic physics courses using the Kahoot application.